Pengaruh Berbagai Media Tanam Terhadap Pertumbuhan Dan Hasil Bawang Merah (Allium ascalonicum L.) - Adinda, Zulya; Syukri, Syukri; Adnan, Adnan (Jurnal Agrotek Lestari, 2025)
This study aims to determine the effect of various planting media on the growth and yield of shallot plants. This study used a non-factorial Randomized Group Design (RAK) method consisting of 16 treatment levels, namely: M1 = Topsoil + Manure + Husk charcoal, M2 = Topsoil + Cow manure + Coconut shell charcoal, M3 = Topsoil + Cow manure + Wood charcoal, M4 = Topsoil + Cow manure + Sawdust charcoal, M5 = Topsoil + Goat manure + Husk charcoal, M6 = Topsoil + Goat manure + Coconut shell charcoal, M7 = Topsoil + Goat manure + Wood charcoal, M8 = Topsoil + Goat manure + Sawdust charcoal, M9 = Topsoil + Chicken manure + Husk charcoal, M10 = Topsoil + Chicken manure + Coconut shell charcoal, M11 = Topsoil + Chicken manure + Wood charcoal, M12 = Topsoil + Chicken manure + Sawdust charcoal, M13 = Topsoil + compost fertilizer + rice husk charcoal, M14 = Topsoil + compost fertilizer + coconut shell charcoal, M15 = Topsoil + compost fertilizer + wood charcoal, M16 = Topsoil + compost fertilizer + sawdust charcoal. The results showed that the treatment of various planting media had a very significant effect on the parameters of plant height at 10, 20, 30 and 40 HST, wet tuber weight, dry tuber weight and a significant effect on tuber weight loss at harvest. The treatment of various planting media did not significantly affect the parameters of the number of tillers at 21 HST and 42 HST, and the number of tubers per clump. The best results were obtained in the M9 treatment (Topsoil: Chicken manure: Rice husk charcoal = 2:1:1).